“Not Just What We Dismantle but also What We Hope to Build”: Alicia Garza on Black Lives Matter and Digital Activism - Clare Mulcahy (Atlantis)
Abstract What follows is an interview with Alicia Garza about Black Lives Matter and the relationship between traditional and digital activism.